Hypertension, medications, and risk of severe COVID‐19: A Massachusetts community‐based observational study. Issue 1 (21st November 2020) - Bauer, Ann Z.; Gore, Rebecca; Sama, Susan R.; Rosiello, Richard; Garber, Lawrence; Sundaresan, Devi; McDonald, Anne; Arruda, Patricia; Kriebel, David
Abstract: It remains uncertain whether the hypertension (HT) medications angiotensin‐converting enzyme inhibitors (ACEi) and angiotensin receptor blockers (ARB) mitigate or exacerbate SARS‐CoV‐2 infection. We evaluated the association of ACEi and ARB with severe coronavirus disease 19 (COVID‐19) as defined by hospitalization or mortality among individuals diagnosed with COVID‐19. We investigated whether these associations were modified by age, the simultaneous use of the diuretic thiazide, and the health conditions associated with medication use. In an observational study utilizing data from a Massachusetts group medical practice, we identified 1449 patients with a COVID‐19 diagnosis. In our study, pre‐infection comorbidities including HT, cardiovascular disease, and diabetes were associated with increased risk of severe COVID‐19. Risk was further elevated in patients under age 65 with these comorbidities or cancer. Twenty percent of those with severe COVID‐19 compared to 9% with less severe COVID‐19 used ACEi, 8% and 4%, respectively, used ARB. In propensity score‐matched analyses, use of neither ACEi (OR = 1.30, 95% CI 0.93 to 1.81) nor ARB (OR = 0.94, 95% CI 0.57 to 1.55) was associated with increased risk of severe COVID‐19. Thiazide use did not modify this relationship. Beta blockers, calcium channel blockers, and anticoagulant medications were not associated with COVID‐19 severity. In conclusion, cardiovascular‐related comorbidities were associated with severe COVID‐19 outcomes, especially among patients under age 65. We found no substantial increased risk of severe COVID‐19 among patients taking antihypertensive medications. Our findings support recommendations against discontinuing use of renin–angiotensin system (RAS) inhibitors to prevent severe COVID‐19.